ANALISIS HIGHEST AND BEST USE (HBU) LAHAN DI KECAMATAN PEDURUNGAN KOTA SEMARANG - Priyambodo, Ronny Achmad; Setiawan, Wahyu (Jurnal Riptek, 2025)
The objective of this study is to determine the highest and best use of vacant land located at Jalan Kompak No. 2-3, Pedurungan District, Semarang City. Data used in this research consist of primary and secondary data. The analysis was conducted using the Highest and Best Use (HBU) method, which considers the physical, legal, financial, and maximum productivity aspects of the vacant land. The physical feasibility analysis examines whether a specific property is suitable to be constructed on a particular parcel of land with its unique characteristics. The legal aspect analysis evaluates compliance with regulations to ensure that the proposed use of the land is permitted by applicable laws. The financial analysis ensures that the project offers economically profitable and financially sustainable outcomes. Meanwhile, the maximum productivity analysis identifies the best return level among the land utilization alternatives. Based on the research, developing the land into a convention hall is identified as the optimal alternative.